Review of the pathology and congenital anomalies of the coracoid process with clinical applications - Lexian McBain; Emily Simonds; Joe Iwanaga; R. Shane Tubbs (Elsevier, 2018)
The coracoid process is an anteriorly projecting, hook-like structure, on the lateral edge of the superior anterior portion of the scapula. The tip of the process points laterally and together with the acromion and their associated ligaments is responsible for stabilizing the shoulder joint. The process articulates with the humerus and clavicle and is the point of attachment for several muscles, the short head of biceps brachii, the coracobrachialis, the pectoralis minor, and also the costocoracoid and conoid ligaments. It is palpable in the deltopectoral groove between the deltoid and pectoralis major muscles. Congenital anomalies of the coracoid process are rare such as bifid coracoid processes. Measurement of the size as well as the angle of the coracoid pillars to the glenohumeral space has been used to provide the anatomical positioning of the coracoid process and has aided in radiographic imaging.